2018
DOI: 10.3390/s18082739
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Emotion Recognition Using Quadratic Time-Frequency Distribution

Abstract: Accurate recognition and understating of human emotions is an essential skill that can improve the collaboration between humans and machines. In this vein, electroencephalogram (EEG)-based emotion recognition is considered an active research field with challenging issues regarding the analyses of the nonstationary EEG signals and the extraction of salient features that can be used to achieve accurate emotion recognition. In this paper, an EEG-based emotion recognition approach with a novel time-frequency featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 69 publications
0
75
0
Order By: Relevance
“…The EEG signals provided by the DEAP dataset [58] New deep learning framework based on a multiband feature matrix (MFM) and a capsule network (CapsNet) is proposed.…”
Section: High/low Arousal and Valencementioning
confidence: 99%
“…The EEG signals provided by the DEAP dataset [58] New deep learning framework based on a multiband feature matrix (MFM) and a capsule network (CapsNet) is proposed.…”
Section: High/low Arousal and Valencementioning
confidence: 99%
“…In [41], KNN method is employed on the DEAP dataset [42] for different numbers of channels which show accuracy between 82% and 88%. The study conducted in [43] quadratic time-frequency distribution (QTFD) is employed to handle a high-resolution time-frequency representation of the EEG and the spectral variations over time. It reports mean classification accuracies ranging between 73.8% and 86.2%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In EEG data channels, typical frequency domain analysis is used. In the frequency domain, the most important frequency bands are delta (1-3 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12)(13), beta (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) [26]. Fast Fourier Transform (FFT), Wavelet Transform (WT), eigenvector and autoregressive are the methods which transform EEG signal from time domain to frequency domain [27].…”
Section: Introductionmentioning
confidence: 99%
“…When Table 12 was examined, it was seen that the proposed method outperformed other methods on HV vs LV discrimination. Alzarzi et al produced a second-best accuracy score where the accuracy was 85.8% (Alazrai et al, 2018). Abeer et al, Tripathi et al and Li et al reported 82.0%, 81.4% and 80.7% accuracy scores, respectively (Al-Nafjan et al, 2017;Tripathi et al, 2017;Li et al, 2017).…”
Section: Experimental Work and Resultsmentioning
confidence: 99%
“…The DEAP dataset was used in experiments and promising results were obtained. Alazrai et al proposed a methodology for EEG based emotion recognition (Alazrai et al, 2018). The authors used a new time-frequency (TF) based features for efficient classification.…”
Section: Introductionmentioning
confidence: 99%